Usefulness of Immunological Detection of the Human Telomerase Reverse Transcriptase - Annalisa Volpi; Sara Bravaccini; Laura Medri; Serenella Cerasoli; Michele Gaudio; Dino Amadori (Cellular Oncology)
Objective: Recent years have seen a considerable wealth of studies conducted on the potential usefulness of telomerase determination in diagnosis, prognosis and targeted cancer therapy. The frequently used Telomeric Repeat Amplification Protocol assay suffers from some drawbacks, the most important being the rate of false positives. In situ analysis using well characterised antibodies directed against the human telomerase reverse transcriptase (hTERT) would therefore appear to be important to morphologically identify the nature of telomerase positive cells. Methods: We performed immunostaining in a series of cultured cells and in normal, preneoplastic and tumour tissues from different organs using a monoclonal antibody directed against the catalytic subunit of telomerase. Results: Immunoreactivity was not observed in perennial cells of terminally differentiated cardiac and skeletal muscular tissues or in small pyramidal cells of the cerebral cortex. Conversely, it was found in other normal somatic tissues as well as in precancerous lesions and in all tumour histotypes. Conclusions: Immunohistochemistry with a well characterised hTERT-specific monoclonal antibody permitted the identification of hTERT immunopositive cells in normal somatic tissues. Whether hTERT protein detected by immunostaining with hTERT-specific Tel 3 36-10 antibody is actually the degraded form of the protein that retains hTERT antigenicity but not enzymatic function, or whether it represents the real, potentially functional catalytic subunit of the enzyme, immunohistochemistry would not seem to represent a useful tool to investigate the role of telomerase and the mechanisms involved in its regulation.